Wavelength dependence and wavelength selectivity in photochemical reactions. Issue 9 (29th January 2019) - Protti, Stefano; Ravelli, Davide; Fagnoni, Maurizio
Abstract : Our study describes how organic photochemists can modify the outcome of a reaction by tuning the wavelength. Abstract : The concepts of wavelength dependence and wavelength selectivity have been commonly used by organic photochemists for a long time. The aim of the present article is to offer a selection of relevant cases where the choice of the irradiation wavelength played a key role in the outcome of a photochemical path. Wavelength dependence can be related to the variation in the efficiency (but not the fate) of a process. Herein, three cases have been recognized where a wavelength-selectivity paradigm operates. Indeed, a different wavelength may (i) activate a different chromophore in a single molecule, (ii) induce the population of different reactive excited states and (iii) sequentially populate the excited state of a compound and the excited state of an intermediate photogenerated from it, which show a different reactivity.